Randomized Trial of Labor Induction in Women 35 Years of Age or Older. Issue 7 (July 2016) - Walker, Kate F.; Bugg, George J.; Macpherson, Marion; McCormick, Carol; Grace, Nicky; Wildsmith, Chris; Bradshaw, Lucy; Smith, Gordon C. S.; Thornton, James G.
Abstract : (Abstracted from N Engl J Med 2016;374:813–822) The average age of women at childbirth in industrialized nations has been increasing steadily for approximately 30 years. The risks of perinatal death, hypertensive disease, gestational diabetes mellitus, placenta previa, and placental abruption are higher among women aged 35 years or older than among younger women.